Transboundary animal disease preparedness and response efforts: disconnects between federal and state levels of government - Crnic, Tarrie A. (Kansas State University, 2010)
Over the past few decades, animal and public health professionals have become increasingly concerned about the global animal population’s vulnerability to Transboundary Animal Diseases (TADs). Through analysis of the lessons learned by the United Kingdom (UK), Taiwan, and Egypt in responding to FMD outbreaks in their countries, it becomes apparent that even with response plans in place at the time of an outbreak, problems still arose as the outbreaks progressed. To better understand why these deviations from the planned course occur, the concept of “disconnects” in the various “domains” of TAD emergency preparedness and response were explored for the United States (U.S.). Particular emphasis was placed on issues related to the collaboration and cooperation between the federal and state levels of government. The domains of communication, knowledge, and resourcing were selected to be analyzed due to their importance in TAD emergency outbreak preparedness and response. The research questions this thesis explores concern three domains of TAD emergency preparedness and response that experience disconnects between federal and state levels of government. They also explore how these disconnects affect Food and Agriculture Security in the U.S. Three different methods were used to research these topics. Literature reviews of lessons learned and after action reports from TAD outbreak exercises and real events were conducted. Direct observations of the author’s experiences at conferences, seminars, and training events were also included. Finally, personal interviews were conducted with Food and Agriculture Security experts. Through this analysis, numerous disconnects emerged in each of the domains. Several disconnects traverse all three domains. These disconnects related to laboratory collaboration with the federal government, the process of declaring a federal emergency, and the roles and responsibilities of individuals and groups involved in TAD outbreak preparedness and response. Overall, the disconnects affect the ability of state and federal governments to rapidly respond to and coordinate response efforts. This affects Food and Agriculture Security by compromising the safety, security, and ongoing operation of the food and agriculture sector. Further study will be needed to alleviate these disconnects so that better cooperation and collaboration can occur between federal and state levels of government.
Keywords: Transboundary animal disease; Foreign animal disease; Emergency preparedness; Federal; Disconnect; Health Sciences, Public Health (0573)